Inherent sex‐dependent regulation of human hepatic CYP3A5. (24th January 2013) - Thangavel, Chellappagounder; Boopathi, Ettickan; Shapiro, Bernard H
Abstract : Background and Purpose: Expression of hepatic cytochromes P450 (CYP) in all species examined, including humans, is generally sexually dimorphic. We examined the sex‐dependent expression of CYP3A5 and the hormone‐regulated molecular mechanism(s) responsible for any dimorphism. Experimental Approach: CYP3A5 levels as well as nuclear translocation and promoter binding of transcription factors regulating CYP3A5 expression were measured in primary hepatocyte cultures derived from men and women exposed to physiological‐like levels of growth hormone alone, dexamethasone alone and the combined regimen. Key Results: We observed a dramatic inherent CYP3A5 sexual dimorphism (women > men) with all treatments as a result of a ∼2‐fold greater level of hormone‐induced activation and nuclear accumulation of hepatocyte nuclear factor‐4α (HNF‐4α), pregnane X receptor (PXR) and retinoic X receptorα (RXRα) in female hepatocytes. Furthermore, PXR : RXRα exhibited significantly higher DNA binding levels to its specific binding motif on the CYP3A5 promoter in female hepatocytes, inferring a possible explanation for the elevated expression of the isoform in women. Results from experiments using HepG2 cells treated with siRNA‐induced knockdown of HNF‐4α and/or transfected with luciferase reporter constructs containing the CYP3A5 promoter were in agreement with the basic mechanism observed in primary hepatocytes of both sexes. Conclusions and Implications: Female‐predominant expression of human CYP3A5 is due to an inherent, sex‐dependent suboptimal activation of the transcription networks responsible for hormone‐induced expression of the isoform in men. Accordingly, in conjunction with previous studies of other human CYPs, men and women are intrinsically unlikely to handle many drugs in the same way; thus, sex should be a requisite component factored into the design of personalized drug therapies.